A comprehensive investigation on wide temperature range rheological properties of polyphosphoric acid modified asphalt - Xiang Liu; Jun Yang; Xiao Li; Liangliang Chen; Shaopeng Zheng; Xiaolong Li (Case Studies in Construction Materials)
Polyphosphoric acid (PPA)-modified asphalt is cost-effective and efficient, but its rheological properties over a wide temperature range and the correlation among various indicators require further quantitative analysis. Therefore, this study focuses on the effects of asphalt sources (three type of asphalt), PPA dosages (0 %, 0.5 %, 1.0 %, 1.5 %), and evaluation indicators. The mechanical properties of PPA-modified asphalt were investigated using the conventional test, temperature sweep test, frequency sweep test, multiple stress creep recovery (MSCR) test, linear amplitude sweep test, and 4 mm DSR test. Differential and correlation analyses were conducted to evaluate the relationship between various rheological performance indicators. The mechanism was then investigated through infrared spectrum. The results show that PPA reduces the temperature sensitivity of asphalt and significantly improves its deformation resistance at high-temperature and low frequencies. There is a strong correlation between various high-temperature performance indicators. Within the linear viscoelastic range, PPA’s effect on asphalt becomes more pronounced at higher temperature. However, in the MSCR test, the effect of PPA increases as the temperature decreases. At low strain, PPA-modified asphalt more effectively mitigates fatigue damage accumulation. But under continuous high strain, PPA adversely affects the asphalt’s fatigue performance. Additionally, PPA increases the asphalt’s sensitivity to stress and strain. At low-temperature, PPA reduces the crack resistance of all three types of asphalt. A higher absorption peak of sulphoxide groups (SO) and phosphate esters (PO) indicates a more pronounced effect of PPA. Furthermore, selecting asphalt that is highly compatible with PPA can reduce the amount of PPA required, thereby lowering modification costs.